Relationship between quadriceps muscle architecture and lower limb strength and physical function in older adults community-dwelling individuals: a cross-sectional study - Cinarli, Fahri Safa; Ulubaba, Hilal Er; Ucar, Ozan; Kilinc, Deniz Can; Ciftci, Rukiye; Karayigit, Raci; Aldhahi, Monira I; Al-Mhanna, Sameer Badri; Gülü, Mehmet (Frontiers in Public Health, 2024)
Background and objective Factors related to muscle architecture may lead to functional limitations in activities of daily living in the older adults. This study aimed to investigate the relationship between quadriceps femoris (QF) architecture and physical function in older adults community-dwelling people. Methods The study included 25 community-dwelling older adults participants aged over 60 years (14 women and 11 men) who were not engaged in regular physical activity. The rectus femoris (RF) and vastus intermedius (VI) muscle thicknesses as well as the RF cross-sectional area (CSA) were assessed using 2D ultrasonography. The 30 Seconds Chair Stand test (30sCST) and Timed Up and Go Test (TUG) were used to assess lower body muscle power and functional mobility, respectively. Results The QF muscle architecture showed moderate and large correlations with the 30sCST (r range = 0.45–0.67, p < 0.05) and TUG (r range = 0.480–0.60, p < 0.05). RF thickness was a significant (p < 0.01) independent predictor of 30sCST (R2 = 0.45) and TUG (R2 = 0.36). VI thickness was a significant (p < 0.05) independent predictor of 30sCST (R2 = 0.20) and TUG (R2 = 0.231). RF CSA was a significant independent predictor of the 30sCST (R2 = 0.250, p < 0.05) and TUG (R2 = 0.27, p < 0.01). Multiple linear regression models explained 38% of the 30sCST variance and 30% of the TUG variance in the older adults group. Conclusion Quadriceps muscle group directly affects basic activities of daily living in the older adults. Ultrasound measurements, which are non-invasive tools, are extremely valuable for understanding the limitations of activities of daily living in the older adults.